2002
DOI: 10.1590/s1519-566x2002000400019
|View full text |Cite
|
Sign up to set email alerts
|

Staphylinidae (Coleoptera) Associated to Cattle Dung in Campo Grande, MS, Brazil

Abstract: Neotropical Entomology 31(4): 641-645 (2002) Staphylinidae (Coleoptera) Associados a Fezes Bovinas em Campo Grande, MS RESUMO -Este trabalho foi executado com o objetivo de determinar as espécies locais de estafilinídeos fimícolas, devido à importância destes predadores e ou parasitóides no controle natural de parasitos de bovinos associadas às fezes. Para tanto, massas fecais com 1, 2 e 3 dias de idade foram coletadas semanalmente em uma pastagem de Brachiaria decumbens Stapf, no período de maio de 1990 a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Among the Scarabaeidae, Dichotomius bos (Blanchard) was the most frequent and constant species. This and other paracoprid species present natural nocturnal and twilight activity (Koller et al 1999(Koller et al , 2002Aidar et al 2000). Because of this and due to the fact that dung pats were collected during the morning period, the paracoprids and telecoprids frequency and constancy may have been underestimated when compared to those of endocoprids that remain in the dung pat.…”
Section: Resultsmentioning
confidence: 99%
“…Among the Scarabaeidae, Dichotomius bos (Blanchard) was the most frequent and constant species. This and other paracoprid species present natural nocturnal and twilight activity (Koller et al 1999(Koller et al , 2002Aidar et al 2000). Because of this and due to the fact that dung pats were collected during the morning period, the paracoprids and telecoprids frequency and constancy may have been underestimated when compared to those of endocoprids that remain in the dung pat.…”
Section: Resultsmentioning
confidence: 99%
“…() and Koller et al . (). These studies have suggested that domination by a few oxyteline species sometimes occurs.…”
Section: Discussionmentioning
confidence: 97%
“…; Davis ; Guimarães & Mendes ; Koller et al . ; Walsh & Posse ; Mendes & Linhares ). Recently, Staphylinidae received special attention for use in forest biodiversity surveys due to their high abundance, diversity, ease of sampling and sensitivity to local environmental conditions (Pohl et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aleochara spp. decreased the population of several fly species developing on bovine faeces, including H. i. exigua (Wright et al , 1989) in Australia and H. irritans in Brazil (Guimarães & Mendes, 1998; Koller et al , 2002; Mariategui et al , 2004). Together with coprophagus colepoterans, histerids were introduced into Australia (Tyndale‐Biscoe, 1996) and the U.S.A. (Fincher, 1995) to evaluate their potential for horn fly control.…”
Section: Alternative Control Strategiesmentioning
confidence: 99%